Evaluation and Design of Squeeze Cementing as a Remedial Effort for High Water Production in Well “MAW-11”at “Mata Allo” Field - Muhammad Arfan Wijaya, S; Firdaus; Amiruddin; Abdul Gafar Karim; Mohammad Lutfi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This study evaluates the feasibility of using a specific cement composition for the abandonment of a non-productive perforated zone at a depth interval of 2631–2640 ft in well MAW-11, located in the Mata Allo Field. Laboratory tests indicate that the cement formulation meets the required performance standards, with a thickening time of 5 hours and 8 minutes at 116 °F and a compressive strength of 2430 psi after 24 hours at 137 °F. Engineering calculations were conducted to determine slurry volume requirements and injection parameters under two scenarios: tight rate injectivity and high rate injectivity. The results show that both scenarios fall within acceptable operational limits. The estimated total cost for the cementing operation is IDR 166,622,550 under tight-rate conditions and IDR 171,493,750 under high-rate conditions. These findings confirm that the cementing plan is both technically feasible and economically viable.